Band Alignment at Heterointerface with Rapid Charge Transfer Supporting Excellent Photocatalytic Degradation of Methylene Blue under Sunlight. Issue 7 (1st February 2022) - Talukdar, Meenakshi; Behera, Sushant Kumar; Jana, Subrata; Samal, Prasanjit; Deb, Pritam
Abstract: Engineering 2D heterostructure using proximitized interfaces is an effective approach to attain high efficiency photocatalytic performance toward dye degradation. Strong interfacial interaction and abundant coupled interfaces and 2D/2D face‐to‐face contact heterostructure facilitate efficient charge separation contributing to high photocatalytic activity. In this aspect, for the first time the authors have analyzed the band alignment of the 2D/2D heterojunction, using Perdew–Burke–Ernzerhof semilocal meta‐generalized‐gradient approximation case and Heyd–Scuseria–Ernzerhof hybrid functional approach in density functional theory stimulation. Close proximity of CuSe nanoflakes with carbon nitride sheets facilitate electron transfer process leading to more proficient photocatalytic degradation, which is confirmed from the inverse participation ratio of individual atoms on the proximitized hetero interface and electrostatic potential line‐ups. The results demonstrate that this 2D/2D heterostructure has desired type‐II band alignment, which is facilitating rapid separation of photogenerated carriers in support of experimental findings. The face‐to‐face contact heterostructure with effective separation and low recombination rate of photogenerated electron–hole pairs helps in complete degradation of dye within 15 min. Further, the brilliance in photocatalytic performance of the developed type II heterostructure correlating with experimental results has introduced this system as a new class of material for wastewater treatment. Abstract : Schematic representation of interaction between 2D/2D van der Waals heterostructure with localized charge distribution for efficient dye degradation is shown.